THE INFLUENCE OF DIGITAL MARKETING DISCOUNTS AND VIDEO COMMERCE ON PURCHASES DECISIONS AMONG STUDENTS OF MUHAMMADIYAH UNIVERSITY OF BENGKULU - Hedias Juliansyah; Andi Azhar (Suluh Adiluhung Publisher (SAPub), 2025)
This article aims to analyze the impact of digital marketing discounts and video commerce on purchasing decisions among students at the University of Muhammadiyah Bengkulu. Using quantitative methods, data were collected through questionnaires distributed to students. The results of the analysis show that digital marketing discounts have a specific impact on purchasing decisions. Likewise, video commerce has been shown to increase students' interest and purchasing decisions. The combination of these two strategies can be used as an effective approach increasing sales among students. This study provides insight for businesspeople and marketers in designing more attractive and effective digital marketing strategies.